The Validity of Skin Conductance For Assessing Acute Pain in Infants: A Scoping Review. Issue 8 (August 2019) - Hu, Jiale; Modanloo, Shokoufeh; Squires, Janet E.; Harrold, JoAnn; Harrison, Denise
Abstract : Objectives: Measuring pain in infants is important but challenging, as there is no "gold standard." The measurement of skin conductance (SC) is considered to be a measure of stress and as a surrogate indicator of pain. The objectives of this study were to identify the extent of research conducted and to synthesize the validity evidence of SC for assessing acute pain in infants. Methods: The Arksey and O'Malley framework for scoping reviews was followed, and 9 electronic databases were searched. Data were analyzed thematically and presented descriptively including the following main categories: study information/details, sampling information, characteristics of participants and settings, SC outcome measures, and validity evidence. Results: Twenty-eight studies with 1061 infants were included, including 23 cross-sectional observation studies and 5 interventional studies. The most studied infants were those with mild severity of illness (n=13) or healthy infants (n=12). The validity evidence of SC was tested in relation to referent pain measures (13 variables), stimuli (13 variables), age (2 variables), and other contextual variables (11 variables). SC was not significantly correlated with vital signs, except for heart rate in 2 of the 8 studies. SC was significantly correlated with the unidimensional behavioral pain assessment scales and crying time rather than with multidimensional measurements. Fourteen of 15 studies (93.3%) showed that SC increased significantly during painful procedures. Conclusions: Inconsistent findings on validity of SC exist. Future research should aim to identify the diagnostic test accuracy of SC compared with well-accepted referent pain measures in infants, study the validity evidence of SC in critically ill infants, and utilize rigorous research design and transparent reporting. Abstract : Supplemental Digital Content is available in the text.